Use of non-steroidal anti-inflammatory drugs and risk of ischemic and hemorrhagic stroke in the Australian veteran community - Mangoni, Arduino A.; Woodman, Richard J.; Gilbert, Andrew L.; Knights, Kathleen M. (Pharmacoepidemiology and drug safety, 2010)
Purpose Studies on the risk of stroke in users of non‐steroidal anti‐inflammatory drugs (NSAIDs) have provided conflicting results. We studied the association between the use of non‐selective ns‐NSAIDs, selective COX‐2 inhibitors, or either of these NSAIDs, and the incidence of stroke‐related hospitalization in elderly subjects. Methods We conducted a retrospective nested case‐control study on Australian veterans using nationwide hospital admission and pharmacy dispensing data. Conditional logistic regression analysis was used to estimate both crude and adjusted odds ratios (OR) and 95% confidence intervals (CI) for the risk of events for three different measures of prescription supply exposure over the last 2 years; (1) whether supplied at least once; (2) supply frequency: supplied more than twice within the last 30 days, once or twice within the last 30 days, or once or more within 30 days to 2 years; and (3) total supplies. Results There was a trend toward a reduced risk of ischemic stroke with any NSAID (OR 0.95, 95%CI 0.89–1.00) if supplied at least once within the last 2 years and a mildly reduced risk in those supplied any NSAID once or twice within the last 30 days (OR 0.89, 95%CI 0.81–0.98). Use of either ns‐NSAIDs or selective COX‐2 inhibitors were not associated with a significant change in risk. Conclusions The use of any NSAIDs is not associated with an increase in the risk of ischemic stroke in Australian veterans. Copyright © 2010 John Wiley & Sons, Ltd.